The Influence of Intellectual Capital on Financial Performance - Amin Wijoyo; Steven Imanuel; Bryan Goodwin (Dinasti Publisher, 2025)
This research aims to obtain observational evidence of the efficiency of capital used, efficiency of human resources, and efficiency of structural capital on financial performance. The independent variables of this research are efficiency of capital used, efficiency of human resources, and efficiency of structural capital, while the independent variable is financial performance. Fabricating companies recorded on the Indonesia Stock Excxhange from 2021-2023 are the populace used in this research. There were 29 tests that met the criteria using the purposive testing method. The model used in this investigate is Microsoft Excel program, and is then handled using the E-views 10 program. The findings from this research are that capital used, human resource efficiency, and structural capital efficiency simultaneously have a significant effect on financial performance. To a large extent, financial performance is significantly influenced by human resource efficiency and structural capital efficiency factors. However, financial performance is not significantly influenced by capital efficiency.